THE EFFECT OF CAFFEINE IN COCOA ON TOOTH MOVEMENT IN ORTHODONTIC TREATMENT - Yusuf, Fika Maziya; Fredina, Finda; Cahyaningrum, Firdayani Agnes; Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2023)
Background: The use of orthodontic appliances for a long time makes it difficult to maintain oral hygiene, so that patients are more susceptible to caries and periodontal disease. Currently, natural ingredients have been used to accelerate tooth movement, one that can be used is the caffeine contained in cocoa. Caffeine can reduce the levels of osteoblasts, Alkaline Phosphatase (ALP), and Osteoprotegerin (OPG) where OPG can inhibit the differentiation and activity of osteoclasts. In addition, caffeine can increase the Receptor Activator of Nuclear factor-Ligand (RANKL), which functions to form and activate osteoclasts, thereby accelerating tooth movement. Purpose: This study aims to determine the effect of caffeine content in cocoa on tooth movement in orthodontic treatment Methods: Analyzed three (3) journals from Google Scholar, PubMed, and ResearchGate. The journal analyzed was the effect of caffeine content in cocoa on tooth movement in orthodontic treatment and the effect of dose and duration of caffeine consumption from chocolate on alveolar bone mineral density on orthodontic tooth movement. Conclusion: This review proves that cocoa contributes to active orthodontic treatment by modulating the rate of tooth movement, inducing osteoclast genesis, and ultimately shortening the duration of orthodontic treatment. Further studies are needed at the clinical level to confirm the efficacy and potential of cocoa in accelerating tooth movement in orthodontic patients.